Analisis Perkembangan Pasar Derivatif di Indonesia - Tanjung, Ahmad Fuadi; Adha, Raju; Marliyah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to analyze the development of the derivatives market in Indonesia. The derivatives market in Indonesia is experiencing rapid growth in response to increasing economic complexity and the need for risk management. This research aims to analyze the development of the derivatives market in Indonesia with a focus on inhibiting factors and opportunities. This research method uses a qualitative approach with a literature study method. Overall, the derivatives market in Indonesia has experienced significant growth in recent years, marked by an increase in futures contract trading volume on the Jakarta Futures Exchange (BBJ). Product innovation, such as stock indices and interest rate futures contracts, as well as the involvement of institutional investors, are the main factors driving this growth. However, the growth of the derivatives market in Indonesia is still relatively slow compared to neighboring countries in the Asian region. The results of this research show that after COVID-19, the derivatives market in Indonesia has bounced back after the fall in the JCI. Governments and markets worked together, addressing risks and recovering well. Derivatives are a solution to manage risk, but education needs to be improved. Despite reforms, challenges remain. This reflects changes and efforts to deal with economic uncertainty.